2019
DOI: 10.1080/21678421.2018.1510011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of impaired voluntary cough function in individuals with amyotrophic lateral sclerosis

Abstract: Objective.-Although cough impairment (dystussia) is common in individuals with amyotrophic lateral sclerosis (ALS) and contributes to a reduced physiologic capacity to defend the airway, characteristics of dystussia have not yet been delineated. We therefore aimed to compare voluntary cough spirometry airflow patterns between individuals with ALS and healthy age and gender matched controls.Methods.-Thirty-two individuals with a diagnosis of probable-definite ALS (El-Escorial Criterion) and 29 healthy age and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…While this work represents the first attempt to examine the discriminant ability and clinical utility of the ALSFRS-R for detecting radiographically confirmed dysphagia, limitations need to be acknowledged. First, following typical analytic methods used in dysphagia research [ 30 , 31 ], the worst PAS score was utilized to determine swallowing safety status, which may have skewed outcomes towards impairment [ 26 ]. Given that we were interested in catching early impairment however, we feel that any potential bias was warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this work represents the first attempt to examine the discriminant ability and clinical utility of the ALSFRS-R for detecting radiographically confirmed dysphagia, limitations need to be acknowledged. First, following typical analytic methods used in dysphagia research [ 30 , 31 ], the worst PAS score was utilized to determine swallowing safety status, which may have skewed outcomes towards impairment [ 26 ]. Given that we were interested in catching early impairment however, we feel that any potential bias was warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, the discriminant ability of the EAT-10 to detect global pharyngeal dysphagia in ALS, has not yet been established. In addition to PROMs, voluntary cough function is noted to significantly differ in individuals with ALS compared to healthy age and gender matched controls, contributing to the impaired ability to effectively expel tracheal aspirate and manage secretions in this population [26]. Given that peak expiratory flow is noted to be reduced by 50% in ALS patients with unsafe swallowing [27], voluntary cough peak expiratory flow (commonly known as peak cough flow testing) has been suggested as a screen to index one's physiologic airway defense capacity [28,29].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, much of the research relating to cough and swallow has shown that single hard cough airflow rates less than approximately 4.5 to 6 L/s (270-360 L/min) are associated with reduced swallow safety and dysphagia. [5][6][7] The research on sequential cough is less robust; however, Hegland and colleagues showed that, in PD, people without penetration or aspiration during swallowing had a more organized cough in terms of peak airflows and durations compared with those who did exhibit penetration or aspiration during swallowing. 8 While the measurement of peak cough airflow for a single There is a growing body of literature examining the use of reflexive, or induced, cough to identify the presence of penetration, aspiration, and swallowing dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary cough motor function can be objectively assessed using a peak flow meter, lending insight into the severity of dystussia 5 and the physiological capacity to cough and protect the airway. Compared with healthy matched controls, voluntary cough strength is noted to be reduced by 36% in individuals with ALS, 4 and those with a cough volume acceleration of less than 45.2 L/s/s were noted to be 5.6‐fold more to likely to penetrate or aspirate during swallowing 2 …”
Section: Introductionmentioning
confidence: 99%